Mega-Events and Mega-Ambitions: South Korea's Rise and the Strategic Use of the Big Four Events - Joo, Yu-Min; Bae, Yooil; Kassens-Noor, Eva (Mega Event Planning, 2017)
This book provides a holistic analysis of South Korea's strategic use of mega-events in its modern development. It examines the Summer Olympics (1988), the World Expo (1993), the FIFA World Cup (2002), and the Winter Olympics (2018) over the past 30 years of the country's rapid growth, and across varying stages of economic and political development. It explains how mega-events helped to secure South Korea's position on the international stage, boost nationalism, propel economic growth in export-oriented national companies, and build cities that accommodate - as well as represent - South Korea's progress. It thereby highlights the broader implications for today's global phenomenon of increasing reliance on mega-events as a catalyst for development, while the criticism that mega-events do more harm than good proliferates. The book is ideal for academics, policymakers, and those with an interest in mega-events and their role in the development of non-western countries.- Resumé vydavatel